A Qualitative Study Exploring Perceptions to the Human T Cell Leukaemia Virus Type 1 in Central Australia: Barriers to Preventing Transmission in a Remote Aboriginal Population - Fowler, Fiona; Einsiedel, Lloyd (Frontiers in Medicine, 2022)
Background Central Australia has the highest recorded prevalence of infection with the human T cell leukaemia virus type 1 (HTLV-1) worldwide. Each of the clinical diseases associated with HTLV-1 have been reported in this region, including deaths due to adult T cell leukaemia, which is causally linked to HTLV-1. Nevertheless, no public health response has been implemented to reduce HTLV-1 transmission among the affected Aboriginal population. In the first study to explore the perceptions of healthcare professionals along with those of Aboriginal people whose communities are actually impacted by HTLV-1, we sought to understand the barriers to preventing HTLV-1 transmission in this remote area. Methodology/Principal Findings Semi and un-structured interviews were conducted with 30 Australian Aboriginal people, 26 non-Aboriginal healthcare professionals and 3 non-Aboriginal community workers. The purpose of the interviews was to explore perceptions towards HTLV-1 in a health context with a focus on sexual and reproductive rights. Deductive and inductive analyses were applied to the data and a decolonizing lens brought peripheral stories to the fore. A major finding was the contrast between views expressed by Aboriginal participants and healthcare professionals regarding the provision of knowledge to those affected. Aboriginal participants consistently articulated that they and their communities should be informed of, and can hold, knowledges pertaining to HTLV-1. This finding controverted the perceptions of healthcare professionals that the complexities of the virus would not be well-understood by their Aboriginal patients and that sharing HTLV-1 knowledges might overwhelm Aboriginal people. Further analyses revealed a spectrum of understanding and clinical practice, while also delineating signs of an imagined public health response. Conclusions/Significance HTLV-1 remains a neglected infection in Australia. Knowledge of HTLV-1 is held by a privileged medical elite and does not flow to marginalised Aboriginal people living in affected communities. We demonstrate that differences in the perspectives of stakeholders presents a significant barrier to the development of cohesive, culturally safe prevention programs that foster a shared knowledge of HTLV-1. The interview data suggests that a successful public health program is likely to require a dual approach that includes clinical care and community-driven health promotion. Aspects of this approach, which would raise awareness and potentially reduce transmission and lower HTLV-1 prevalence in Central Australia, may be applicable to other endemic settings with similar conditions of social disadvantage, geographic remoteness, resource limitations and cross-cultural challenges.